Antinociceptive Antibiotics-Loaded into Solid Lipid Nanoparticles of Prolonged Release: Measuring Pharmacological Efficiency and Time Span on Chronic Monoarthritis Rats - Laurido-Fuenzalida, C; Martinez-Salinas, J (Public Library of Science, 2018)
Pain is a sensory experience of a complex physiological nature in which is not only involved the nervous system. Among its many features is the development of chronic pain that is more complicated to treat because of the central somatization processes involved, becoming inefficient treatments used in other forms of pain. Among them is the role of glial cells, whose participation is such that some authors have proposed to chronic pain as a gliopathy. Because of this, the drug target of possible treatments focuses on modulating nociceptive response affecting transduction into the central nervous system through affecting synapses in the dorsal horn of the spinal cord. Solid lipid nanoparticles enter the central nervous system, protecting the drug, and in addition to the advantage of having greater absorption surface, all factors that improve drug activity. This work is based on the development and characterization of lipid nanoparticles of solid phase incorporating two antibiotics, minocycline, and ciprofloxacin with antinociceptive properties and challenged them with a rat monoarthritis model using Sprague-Dawley adult male rats. The solid lipid nanoparticles were prepared to modify the lipid, and surfactant amounts to obtain the best encapsulation capacity of the antibiotics, size and z potential. By using the Randall-Selitto test, we measured its pharmacological efficiency as an anti-inflammatory and measuring the time span the antibiotics are active. The encapsulated antibiotics were at least 50% more efficient than the antibiotic alone, and that is possible to measure anti-inflammatory activity up to seven days after the antibiotic application. The former is important for example, in the veterinary field, since a single application of the antibiotic will be necessary for the complete treatment, avoiding excessive stress for the animals. We can conclude that antinociceptive antibiotics encapsulation is a very effective, environmentally safe and inexpensive method for improving the pharmacological efficiency and time span the antibiotics are acting. Since these antibiotics are both anti-microbial and antinociceptive, his use in the field of veterinary presents the advantage of being adequate in single doses, with the saving of time and stress to the animals under treatment. © 2018 Valdes et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.